Agro-commodity dependence and recent trends in agro-commodity markets - Peter Gibbon (Danish Institute for International Studies (DIIS), 2007)
This paper examines trends in agro-commodity trade over the decade to 2005, in relation to the changing patterns of import demand and price trends, globally and in Developing Asia. It also examines the performance of 'commodity-dependent developing countries' (CDDCs) in agrocommodity trade. It finds that the 'commodity boom' does not extent to agro-commodities, although demand in Developing Asia is becoming an increasingly important factor, at least in less differentiated market segments. The agro-commodity trade performance of CDDCs is weak and apparendy declining. The paper goes onto discuss reasons for the latter and to suggest policies that may mitigate these trends.
Keywords: 330; Agrarprodukt; Rohstoffressourcen; Rohstoffpolitik; Agraraußenhandel; Entwicklungsländer; Asien